Community Empowerment at The Intersection of Public Health and Green Entrepreneurship: A Case Study of Bank Sampah-Posyandu Collaboration - Nurhayati, Sri; Rusmayati, Titin; Boriboon, Gumpanat (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the integration of green economy principles and community empowerment through the collaboration between Bank Sampah Berkah Kenanga and Posyandu in Desa Sayati. The research aims to analyze how waste management initiatives can simultaneously promote financial literacy, economic resilience, and environmental stewardship at the grassroots level. A qualitative approach was adopted, with data collected through structured interviews involving waste bank managers, Posyandu cadres, and community members. Results show that the “Bawa Sampah Selalu ke Posyandu” (BAWASLU) program links monthly child health monitoring sessions with systematic waste collection, allowing residents to convert household waste into savings redeemable for essential goods or precious metals. Participants reported increased financial literacy, household savings, and social capital, alongside greater environmental awareness and leadership opportunities, particularly for women. Intergenerational transmission of sustainable practices was also observed. However, operational challenges persist, notably manpower shortages, logistical inefficiencies, and limited mechanization. Despite these constraints, the collaboration demonstrates significant potential for replication and expansion through capacity-building initiatives, policy support, and formalization into a cooperative structure. In conclusion, the Bank Sampah–Posyandu model presents an innovative and effective framework for linking public health objectives, environmental sustainability, and socioeconomic development in rural communities. Future efforts should focus on infrastructure investment, digital marketing expansion, and intensified environmental education to optimize program scalability and long-term impact.